STRATEGI DAN PRINSIP UTAMA PENGEMBANGAN KURIKULUM PAI UNTUK OPTIMALISASI PEMBELAJARAN - Habib Zainuri; Almaimani, Abdus Salam; Farhan; Deyan Nugraha, Muhammad Raezhard (STAI Pelabuhan Ratu, 2024)
This study examines the key strategies and principles in developing the Islamic Religious Education (PAI) curriculum, aiming to optimize the learning process. The study addresses the issue that the current PAI curriculum tends to focus on cognitive aspects without adequately considering the application of religious values in daily life. The method employed is library research, analyzing various literature related to curriculum development and Islamic education. The results show that an ideal PAI curriculum must balance the mastery of subject matter and the character development of students. A competency-based approach, which includes cognitive, affective, and psychomotor aspects, is recommended for curriculum development. This study also highlights the importance of incorporating technology into education to create a more interactive learning experience. In conclusion, the development of the PAI curriculum must continuously adapt to social and cultural dynamics to equip students with the necessary skills to face contemporary challenges and succeed in the modern world.